Exploring the Impact of Kisspeptin-10 on the Fecundity Traits of Anestrus Iraqi Cows - Khafaji, S. S. (Tropical Animal Science Journal, 2024)
The inactive ovaries of cattle caused a significant economic loss, so the current study is intended to recover and enhance the fertility of dairy cattle suffering from anestrus by kisspeptin-10. Forty Holstein Friesian cows, aged 3.5-6.8 years with inactive ovaries for 60-70 days of postpartum, were distributed randomly into four equal groups. The control (C) group administered 5 mL intramuscularly (I.M) of normal saline, Gn group administered 0.5 mg/animal I.M of GnRH. K1 and K2 were administered with 6 μg/kg BW I.M and 12 μg/kg BW I.M of kisspeptin-10, respectively. After heat signs were detected, artificial insemination was performed. Blood samples were collected at 0, 2, 6, 24, and 72 hours post-hormonal injection to estimate fertility hormones, and fecundity features were demonstrated after hormonal treatment and after twelve months. The current results noted a significant (p